Utilization of periwinkle and palm kernel shells in load-bearing ecofriendly interlocking concrete paver - Olofinnade, Oluwarotimi; Awoyera, Paul; Edemirukewa, Kelvin; Ogundipe, Kunle (Frontiers in Built Environment, 2025)
In recent times, increasing demand for raw aggregate has emphasized the need for construction industry to adopt sustainable practices by exploring alternative materials, such as agro-waste, to address resource depletion and reduce environmental pollution., This current study investigated the suitability of combining discarded periwinkle shell (PWKS) and palm kernel shell (PMKS) at low-replacement volumes to partially substitute granite in ecofriendly load-bearing cement-based interlocking paver units for use on medium-duty traffic roads. 108 paver samples were produced, targeting a 28-day strength of 30 MPa, using a mix proportion of 1:1:2 (cement: sand: granite) and water-cement ratio of 0.50. Physical and chemical compositions of materials are examined, while the produced paver samples were tested for their water absorption, compressive and split-tensile strengths properties. The influence of curing (immersion and open air) on the strength development was evaluated. Findings showed that the shells recorded low physical properties but increased water intake tendency. A gradual decrease in the strength performances of the pavers was observed as the amount of PWKS and PMKS increases in the mixes. The water absorption tendency increases with increasing PMKS and PWKS levels. Pavers cured by complete immersion in water recorded good strength and achieved the 30 MPa compared to open air cured pavers. This study recommends load-bearing pavers of up to 30 MPa can be made by combining PMKS and PWKS at a low-replacement level of 5% deployed for medium-traffic roads, but with adequate curing technique. Outcomes showed the viability of incorporating periwinkle and palm kernel shells as aggregate in making standard paver units of adequate strength and resistance to water to promote sustainable construction practices.